Pre and Post-COVID-19 Share Trading: Case of Australia and Southeast Asia - Suwaldiman, Suwaldiman; Syah Putra, Galih Wisnu (Department of Accounting, Faculty of Economics & Business, 2025)
This research aims to analyze the share prices and trading volume activity in the pharmaceutical industry in Southeast Asia and Australia during the pre-and post-COVID-19 periods. The data sample includes pharmaceutical companies listed in Southeast Asian countries and Australia from 2017 to 2022. The analysis utilizes monthly closing price data for 36 months before COVID-19 (2017-2019) and 36 months after (2020-2022). The data were processed and analyzed using the Wilcoxon Signed Rank Test. The findings indicate that there are significant differences in share prices and trading volume activity in the pharmaceutical industry between the pre-and post-COVID-19 periods. Specifically, the research reveals differences in share price and trading volume in Australia, Indonesia, Malaysia, Vietnam, and Thailand. In contrast, no significant differences were observed in share prices and trading volumes in Singapore and the Philippines. It is important to note that the study only included a sample of the pharmaceutical industry from six Southeast Asian countries and one country from Oceania (Australia). The number of pharmaceutical samples varied across these countries, with the Philippines represented by only one sample. Therefore, generalizations about all listed companies in these countries cannot be made. Future research should consider increasing the sample size by expanding the scope to include more regions or countries. Additionally, employing regression analysis to examine the influence between variables is recommended.